ELSAH (electronic smart patch system for wireless monitoring of molecular biomarkers for healthcare and wellbeing): definition of possible use cases - Brinkmann, Christian; Bloch, Wilhelm; Mutinati, Giorgio C. (Frontiers in Bioengineering and Biotechnology, 2023)
The ELSAH (Electronic smart patch system for wireless monitoring of molecular biomarkers for healthcare and well-being) project has received funding from EU’s Horizon 2020 research and innovation program (grant agreement no. 825549). Its aim is to develop a wearable smart patch-based microneedle sensor system that can simultaneously measure several biomarkers in users’ dermal interstitial fluid. This system could have several use cases based on continuous glucose and lactate monitoring: early detection of (pre-)diabetes mellitus, increasing physical performance through optimal carbohydrate intake, achieving a healthier lifestyle through behavioral changes based on the interpretation of glucose data, performance diagnostics (lactate threshold test), control of optimal training intensities corresponding with certain lactate levels, or warning of diseases/health threats, such as the metabolic syndrome or sepsis associated with increased lactate levels. The ELSAH patch system has a high potential of increasing health and well-being in users.